Lithium‐Ion Batteries: Hollow TiO2 as an Anode for Lithium Ion Batteries: Synthesis and In Situ Visualization of State of Charge (Adv. Electron. Mater. 12/2015). (December 2015) - Huang, Xingkang; Cui, Shumao; Wieboldt, Richard C.; Hallac, Peter B.; Fell, Christopher R.; Metz, Bernhard; Jiang, Junwei; Chen, Junhong
Abstract : In article number 1500256, Junhong Chen and co‐workers introduce a facile synthesis method for hollow TiO2 using CaCO3 as a template. The resulting hollow TiO2 exhibits a high capacity with excellent cyclic performance when used as an anode for lithium ion batteries. The lithiation mechanism of the TiO2 anode is also investigated by using an in situ Raman spectroscopic imaging technique.